(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
This article will critically examine the status and scenario of Human Rights of Baiga Tribes in Central India. The Baiga Tribal community in Central India has been the most vulnerable community in Central India. The socio, economic, political and cultural rights of Baiga Tribes have been violated. Even after 69 years of Independence, the conditions of Baiga Tribal communities have not been improved. The fundamental human rights of Baiga tribes have been violated and discrimination, suppression and brutality have been perpetrated on them, particularly on Baiga tribal women. Baiga Tribal communities have faced social discrimination and isolation in Central India. The historical factors have determined the political, ideological, social, cultural and economic life of the Tribal communities. The Constitution of India, National Human Rights Commission, Ministry of Tribal Affairs, National Commission for Scheduled Tribes have been strongly advocating for social justice and Human Rights of Baiga tribes. Despite these developments, the democratic experiment has not been succeeded in this endeavor. In this context, therefore, there is need for emergence of Baiga Tribal movements in Central India to protect their human rights. This article will critically analyze status of Human Rights of Tribes within the larger framework of human rights in general and how the human rights of Baiga tribes have been violated in Central India in particular. Further, the article will critically examine various welfare policies of Ministry of Tribal Welfare, Government of India for the empowerment of Baiga Tribal society in contemporary Indian Democracy. It will also critically analyze the role of the Indian Constitution to create an egalitarian tribal society in India, which is based in equality, liberty, justice and fraternity. The Constitution of India provides and guarantees justice, social, economic and political rights for all citizens. The constitutions makers realized that the inequitable forces have been deeply involved in the socio, economic and political system of the society. Finally, it has been resulted in the in deprivation and disadvantage of the marginalized, deprived and the weaker sections of the society. Further, it will also examine constitutional safeguards for the empowerment of Baiga Scheduled Tribes in Central India.